Theory of the Development of Safety in Codes of Practice - Proske, Dirk; ICASP14 (My University, 2023)
Nowadays, the required safety of structures is achieved in codes of practice through computational verifications and qualitative requirements, e.g., on the building materials and the construction processes. Both the computational verifications and the qualitative requirements are shaped by increasingly specific scientific investigations and by political framework conditions. The target values of the required safety are largely developed by theoretical models, such as Life Cycle Cost Analysis, Life Quality Index etc., although individual collapses have an impact on the codes. An examination of safety across all structures has not yet been carried out. In this paper, the safety of structures is determined from the ratio of the median calculated failure probabilities of different calculations and the median observed collapse frequencies over all structures. The ratio shows the absolute safety, i.e., the sum of safety from computational verifications, qualitative requirements, and any further requirements in codes. This also allows an assessment of the quality of research and standardization work. For example, the difference in the collapse frequency of Italian road bridges under traffic load and road bridges in many other developed countries may be an indicator for insufficient maintenance. Also, the difference in the collapse frequency of buildings in developed and developing countries may be an indicator for insufficient training for persons on the construction site in developing countries. Furthermore, the paper introduces the theory, that the ratio of median collapse frequencies and probabilities of failure are time dependent, like a velocity of change of safety. Numbers are given for certain types of structures. However, the ratio is not moving straight forward but in cycles. It is further assumed that this theory is not only valid for structures, but also for other technical products. Finally, parameters are suggested for the conversion of the failure probability into the collapse frequency for bridges, retaining walls and earth structures.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED